2016
DOI: 10.1259/bjr.20160476
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric evaluation of low grade gliomas at follow-up: comparison between diffusion and perfusion MR with 18F-FDOPA PET

Abstract: Objective: To compare MRI using perfusion and diffusion techniques with 6-[ LGGs) and to identify the best imaging parameter to differentiate patients with different prognosis. Methods: Between 2010 and 2015, 12 patients with a pathology-proven diagnosis of LGG and MR (with perfusion and diffusion sequences) and a PET study during their follow-up were retrospectively included in our study. Cerebral blood volume (CBV) and apparent diffusion coefficient (ADC) maps on MR studies and PET images were evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Briefly, 18 F-FDopa, is mainly integrated in cells by L-Amino-acid Transporter 1 (LAT 1), which is overexpressed in gliomas [5]. 18 F-FDopa PET allows to distinguish glioblastoma from other gliomas but its contribution to prognosis remains debated inside a same grade, particularly to stratify newly diagnosed low-grade gliomas [4,6,7]. Up to now, only two studies have reported a prognostic value of 18F-FDopa uptake in low-grade gliomas for disease progression [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, 18 F-FDopa, is mainly integrated in cells by L-Amino-acid Transporter 1 (LAT 1), which is overexpressed in gliomas [5]. 18 F-FDopa PET allows to distinguish glioblastoma from other gliomas but its contribution to prognosis remains debated inside a same grade, particularly to stratify newly diagnosed low-grade gliomas [4,6,7]. Up to now, only two studies have reported a prognostic value of 18F-FDopa uptake in low-grade gliomas for disease progression [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…18 F-FDopa PET allows to distinguish glioblastoma from other gliomas but its contribution to prognosis remains debated inside a same grade, particularly to stratify newly diagnosed low-grade gliomas [4,6,7]. Up to now, only two studies have reported a prognostic value of 18F-FDopa uptake in low-grade gliomas for disease progression [6,7]. Nevertheless, the relationship with molecular parameters was not evaluated; the first one did not provide semi-quantitative ratios [6], and the second one involved a weak number of patients (n=12) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 On-line Table 2 summarizes the various PET radiotracers and their uptake mechanism, half-life, availability, and uptake in the healthy brain. We will discuss the most commonly used FDG, 32-37 and other various radio-labeled AATs such as 11 C-MET), 32,36,38-42 6[ 18 F]fluoro-L-dopa (FDOPA), [43][44][45] and [ 18 F]fluoroethyl-L-tyrosine (FET), [46][47][48][49][50][51] as well as 18 F-fluorothymidine (FLT), 50,52 which evaluates DNA syntheses (On-line Table 3).…”
Section: Perfusion-weighted Imagingmentioning
confidence: 99%
“…Hence, the use of various AATs has been proposed. 32,33,36,52 Amino Acid Transport and Protein Synthesis PET with AAT-11 C-MET, 32,36,39,40,42 [ 18 F] FET, [46][47][48][49][50] and [ 18 F] FDOPA 33, [43][44][45] has shown remarkable results in evaluating posttreatment changes of gliomas. Radiolabeled AATs show high tumor-to-background ratio (TBR) in gliomas because of increased cell proliferation and extracellular matrix production.…”
Section: Glucose Metabolism: Fdg-petmentioning
confidence: 99%